A Review Article on Transdermal Drug Delivery System Based On- Microneedles - Butola, Kanchan (Journal for Research in Applied Sciences and Biotechnology, 2022)
Every drug delivery system should work toward preserving the drug's appropriate dose and facilitating its full metabolism within the body. Transdermal delivery of very large ionic and hydrophilic molecules is made possible by the microneedle array. Studies on the effectiveness of microneedles have been conducted extensively. Soon, the market for commercial microneedle-based goods will grow, and they may eventually have a major impact on clinical medicine. This article provides an overview of microneedles, discussing their history, many varieties, current state, potential applications, and recent technological developments.